Effect of pre-sowing seed treatments in Magnolia gustavii King – a 'Critically Endangered' timber yielding species of North-East India - Borah, Ellora Dutta; Saikia, Ankur Jyoti; Borua, Namrata; Borah, Rajib Kumar (Indian Forester, 2025)
No Abstract.